Hubungan Faktor yang Memengaruhi Indeks Prestasi Kumulatif dan Student Activities Performance System Mahasiswa Fakultas Kedokteran Universitas Andalas - Devin Mahendika; Multazam Fahreza Chandra; Ema Julita (Jurnal Ners, 2023)
This study aims to determine the relationship between factors that influence the cumulative grade point average and student activity performance system for Andalas University medical faculty students. This research is a categorical analytic study with a cross-sectional design. Sampling using simple random sampling technique to obtain 162 respondents. The research was conducted from February 2020-2021 on FK UNAND students class of 2016. The research data was obtained by filling out a questionnaire and guided interviews. The results showed that there was a significant relationship between entry, UKT, parental education, National Examination scores, and talent interest with GPA. In addition, there is no significant relationship between entry, UKT, parental education, National Exam scores and SAPS and there is a significant relationship between interest in talent and SAPS.